Acute Respiratory Failure in Acute Poisoning by Neutrotropic Substances - A. N. Lodyagin; G. A. Livanov; I. P. Nikolayeva; B. V., Batotsyrenov; G. V. Shestova; N. S. Fedicheva; L. D. Tsvetnova; Kh. V. Batotsyrenova (Общая реаниматология, 2008)
Objective: to evaluate the efficiency of methods for diagnosing and treating critically ill patients with acute respiratory failure (ARF) in acute poisoning by neurotropic substances. Subjects and methods. Two hundred and thirty-three patients with acute severe intoxication with neurotropic poisons were examined. All the patients were admitted for toxic-hypoxic coma and ARF; in this connection all the patients underwent artificial ventilation (AV). The patients were divided into 3 groups: 1) those in whom the traditional treatments (AV, detoxifying therapy, and infusional and cardiotropic support) could restore the basic parameters of vital functions, as judged from the recovered oxygenation index; these patients had no metabolic shifts; 2) those who had signs of pulmonary hyperhydration, low cardiac output and moderate metabolic disorders, as suggested by elevated lactate levels; 3) seriously ill patients in whom the interval between the time of poisoning to care delivery was more than 20 hours; the patients of this group had the most significant metabolic disorders. Results. Correction of ARF in critically ill patients with acute poisoning should include, in addition to the rational parameters of AV and detoxifying therapy, agents for targeted therapy for sequels of hypoxia and energy deficiency states. For maximally rapid and effective oxygen transport recovery, the addition of perfluorane to the complex therapy cardinally improves the results of treatment and reduces mortality rates. Conclusion. The complexity of the pathogenesis of ARF and its sequels is a ground for diagnosing and correcting not only ventilation disturbances, but also pulmonary microcirculatory disorders and metabolic disturbances. Key words: acute intoxication with neu-rotropic poisons, acute respiratory failure, pulmonary hyperhydration, hypoxia, metabolic disturbances.